Synthesis and Characterization of Zirconium Oxide (ZrO2) Films on AA5052 and Glass substrates. Issue 1 (February 2021) - Madhusudhana, R; Navyashree, K C; Krishnamurthy, L.; Gopalakrishne Urs, R
Abstract: Aluminum alloy has gained lot of importance in Aerospace Industries and Engineering applications because of its strength, high resistance to heat, light weight and durability. In this paper we made an attempt to improve the AA5052 substrates properties by coating Zirconium Oxide (ZrO2 ) by Sol-Gel Method. Glass substrates were also coated with Zirconium Oxide (ZrO2 ) coating. The coated AA5052 and glass substrates will be annealed to check the thermal resistance for various time of thermal rig test. Micro crystalline properties and formation of ZrO2 of the coated film is evaluated for surface morphological studies by using Scanning Electron Microscope (SEM) and the elemental composition studies done by EDAX (Energy Dispersive Absorption X-ray Spectrometer).